The gene ontology of eukaryotic cilia and flagella - Roncaglia, Paola; Nacheva, Lora (Cilia, 2017)
Recent research into ciliary structure and function provides important insights into inherited diseases termed ciliopathies and other cilia-related disorders. This wealth of knowledge needs to be translated into a computational representation to be fully exploitable by the research community. To this end, members of the Gene Ontology (GO) and SYSCILIA Consortia have worked together to improve representation of ciliary substructures and processes in GO.
Gesehen am 12.04.2018